Asociación entre la frecuencia de giardiasis intestinal y nivel de hemoglobina en niños menores de 5 años - Hernández Hernández, Lucy Alicia (2010)
It was performed a descriptive comparative study in children under five years old at Centro de Salud Salaverry- Trujillo during the year 2005 in order to determine the association between the frequency of intestinal giardiasis and hemoglobin levels. The sample included 96 children procedent and residents in the north coast of Salaverry; 48 of them with diagnostic of intestinal giardiasis (cases), and 48 without this diagnostic (control group). The coproparasitological study was performed with direct method in fresh with physiological saline solution for identification of Giardia lamblia in 3 alternate days. The level of hemoglobin was measured with the cyanmethahemoglobin method. Results: The frequency of low hemoglobin level for the children age was of 33 (69%) of the cases and 5(10%) of control group, with significant statistical difference. Conclusions: The low level of hemoglobin in children under 5 years old, attended at Centro de Salud Salaverry-Trujillo, in 2005, is often associated in children with intestinal giardiasis compared with those who don’t suffer this disease.